Augmented Reality-Centered Position Navigation for Wearable Devices with Machine Learning Techniques. (7th April 2022) - Kamalam, G. K.; Joshi, Shubham; Maheshwari, Manish; Selvan, K. Senthamil; Jamal, Sajjad Shaukat; Vairaprakash, S.; Alhassan, Musah
Abstract : People have always relied on some form of instrument to assist them to get to their destination, from hand-drawn maps and compasses to technology-based navigation systems. Many individuals these days have a smartphone with them at all times, making it a common part of their routine. Using GPS technology, these cellphones offer applications such as Google Maps that let people find their way around the outside world. Indoor navigation, on the other hand, does not offer the same level of precision. The development of indoor navigation systems is continuously ongoing. Bluetooth, Wi-Fi, RFID, and computer vision are some of the existing technologies used for interior navigation in current systems. In this article, we discuss the shortcomings of current indoor navigation solutions and offer an alternative approach based on augmented reality and ARCore. Navigating an indoor environment is made easier with ARCore, which brings augmented reality to your smartphone or tablet.